Formulation and Characterization of Curcumin-Loaded Microsponge Gel for Controlled Release and Enhanced Stability in Topical Antioxidant Therapy - Emma Jayanti Besan; Muhammad Nurul Fadel; Nur Masyithah Zamruddin; Husnunnisa; Cut Intan Annisa Puteri (Fundamental and Applied Research in Medicine and Allied Sciences Indonesia, 2026)
Curcumin possesses strong antioxidant and photoprotective activities, but its poor aqueous solubility, limited skin penetration, and high photoinstability restrict topical efficacy. This study developed curcumin-loaded microsponges using Eudragit RS100 by the quasi-emulsion solvent diffusion method. The optimized formulation (MS-F5) showed high encapsulation efficiency (91.7 ± 1.6%), porosity (61.3 ± 2.8%), positive zeta potential (+28.3 ± 2.1 mV), and sustained 24-h drug release following Higuchi kinetics (R² = 0.9952). Incorporated into a 2% Carbopol gel, MS-F5 significantly enhanced skin permeation (2.89-fold), epidermal retention (3.52-fold), antioxidant activity (IC₅₀ 12.4 ± 0.8 vs. 18.7 ± 1.2 µg/mL), and photostability (72.4% vs. 18.3%) compared with plain curcumin gel (p < 0.05). Stability studies following ICH Q1A(R2) and Q1B guidelines confirmed acceptable physicochemical and microbiological stability over six months. These findings demonstrate that microsponge technology improves curcumin stability, controlled release, skin delivery, and antioxidant performance, highlighting its potential for dermatological and cosmeceutical applications.